Effect of crystal orientation on corrosion behavior of directionally solidified Mg-4 wt% Zn alloy. Issue 7 (July 2018) - Jia, Hongmin; Feng, Xiaohui; Yang, Yuansheng
Abstract: Microstructure and crystallographic orientation of directionally solidified Mg-4 wt% Zn alloy were characterized by X-ray computed tomography (XCT) and electron backscatter diffraction (EBSD) in this study. Results reveal that Mg-4 wt% Zn alloy with dendritic microstructure exhibits typical 0002 basal texture along growth direction. Based on this, the effect of grain orientation on corrosion behavior of directionally solidified Mg-4 wt% Zn alloy in 0.9 wt% NaCl solution was investigated. Result shows that 0002 oriented planes have better corrosion resistance than 11 2 ¯ 0 and 10 1 ¯ 0 ones, which is attributed to a synergistic effect of surface energy, atomic packing density and the stability of oxidation film.